If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4g + -7 = 9g + 3 Reorder the terms: -7 + 4g = 9g + 3 Reorder the terms: -7 + 4g = 3 + 9g Solving -7 + 4g = 3 + 9g Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-9g' to each side of the equation. -7 + 4g + -9g = 3 + 9g + -9g Combine like terms: 4g + -9g = -5g -7 + -5g = 3 + 9g + -9g Combine like terms: 9g + -9g = 0 -7 + -5g = 3 + 0 -7 + -5g = 3 Add '7' to each side of the equation. -7 + 7 + -5g = 3 + 7 Combine like terms: -7 + 7 = 0 0 + -5g = 3 + 7 -5g = 3 + 7 Combine like terms: 3 + 7 = 10 -5g = 10 Divide each side by '-5'. g = -2 Simplifying g = -2
| 2(x+3)-2=4x-2x+4 | | g=11xy | | -10+3x^2-12x=0 | | (3)(3.14*r^2)=13 | | q+36=4q | | F(x)=x^2+9*x | | P*2x=2*4*2x | | 1.25+.66q= | | -33-[2+5y-7(y-2)]=-11(2y-5)-[5(y-1)-3y+3] | | 3x^2+12x=-26 | | 4(x-1)-2(x+5)=32 | | sqrt(4z+9)=z+1 | | 8z^3-12z^2+10z-3=0 | | 7x-(8x+8)=x-9 | | 10-3q=1 | | 4(2+3x)=5 | | h=-64t^2+qt+k | | 392*x=49 | | 69x=690 | | 40x+34=634 | | 2x+32=7x+7 | | x(2x+21)=180 | | p(x)=x^2-7x-10 | | x^2+a^2-14x-10a+58=0 | | 4(x-1)+13=x-3(x+1) | | 5+2y=15-3y | | G=9/4(p-1) | | 30=5c+20 | | 15-27b+11=-244 | | 46+X=349 | | 5x-1=2x-5 | | LOG(7)(4-X)=1 |